\[\boxed{\text{1214\ (1214).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ f(x) =\]
\[= (x - 1)(x + 1) - x(x - 3) =\]
\[= x^{2} - 1 - x^{2} + 3x = 3x - 1 -\]
\[линейная:\]
\[x\] | \[0\] | \[1\] |
---|---|---|
\[f\] | \[- 1\] | \[2\] |
\(.\)
\[2)\ f(x) =\]
\[= (2x - 3)^{2} - (x + 4)(x - 2) =\]
\[= 3x^{2} - 14x + 17 -\]
\[нелинейная.\]
\[3)\ f(x) = (x + 3)^{2} - x(x + 6) =\]
\[= x^{2} + 6x + 9 - x^{2} - 6x = 9 -\]
\[линейная:\]
\(\text{.\ }\)
\[\boxed{\text{1214.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ (0;0):\]
\[\left\{ \begin{matrix} y - x = 5\ \ \ \ \\ 3x + 2y = 4 \\ \end{matrix} \right.\ \]
\[\left\{ \begin{matrix} 0 - 0 = 5 \\ 0 + 0 = 4 \\ \end{matrix} \right.\ \]
\[\left\{ \begin{matrix} 0 \neq 5 \\ 0 \neq 4 \\ \end{matrix} \right.\ \]
\[верно.\]
\[2)\ ( - 1;2):\]
\[\left\{ \begin{matrix} x + y = 1\ \ \ \ \ \ \ \ \\ 3x + 2y = - 1 \\ \end{matrix} \right.\ \]
\[\left\{ \begin{matrix} - 1 + 2 = 1\ \ \ \\ - 3 + 4 = - 1 \\ \end{matrix} \right.\ \]
\[\left\{ \begin{matrix} 1 = 1\ \ \ \\ 1 \neq - 1 \\ \end{matrix} \right.\ \]
\[верно.\]